P97 dysfunction underlies a loss of quality control of damaged membrane proteins and promotes oxidative stress and sickling in sickle cell disease. Issue 5 (11th April 2022) - Song, Anren; Wen, Alexander Q.; Wen, Y. Edward; Dzieciatkowska, Monika; Kellems, Rodney E.; Juneja, Harinder S.; D'Alessandro, Angelo; Xia, Yang
Abstract: Sickling is the central pathogenic process of sickle cell disease (SCD), one of the most prevalent inherited hemolytic disorders. Having no easy access to antioxidants in the cytosol, elevated levels of reactive oxygen species (ROS) residing at the plasma membrane in sickle red blood cells (sRBCs) easily oxidize membrane proteins and thus contribute to sickling. Although the ubiquitin‐proteasome system (UPS) is essential to rapidly clear ROS‐damaged membrane proteins and maintain cellular homeostasis, the function and regulatory mechanism of the UPS for their clearance in sRBCs remains unidentified. Elevated levels of polyubiquitinated membrane‐associated proteins in human sRBCs are reported here. High throughput and untargeted proteomic analyses of membrane proteins immunoprecipitated by ubiquitin antibodies detected elevated levels of ubiquitination of a series of proteins including cytoskeletal proteins, transporters, ROS‐related proteins, and UPS machinery components in sRBCs. Polyubiquitination of membrane‐associated catalase was increased in sRBCs, associated with decreased catalase activity and elevated ROS. Surprisingly, shuttling of p97 (ATP‐dependent valosin‐containing chaperone protein), a key component of the UPS to shuttle polyubiquitinated proteins from the membrane to cytosol for proteasomal degradation, was significantly impaired, resulting in significant accumulation of p97 along with polyubiquitinated proteins in the membrane of human sRBCs. Functionally, inhibition of p97 directly promoted accumulation of polyubiquitinated membrane‐associated proteins, excessive ROS levels, and sickling in response to hypoxia. Overall, we revealed that p97 dysfunction underlies impaired UPS and contributes to oxidative stress in sRBCs.